QUALITATIVE ANALYSIS OF DEPENDENCE OF DRIVE POWER HORIZONTAL-INCLINED BELT CONVEYOR ON ITS INITIAL PARAMETERS - Bohomaz, V. M.; Borenko, M. V.; Nechay, I. V.; Severyn, O. P. (Science and Transport Progress, 2017)
Purpose.One of the main elements of band conveyors is a drive. To analyze the effect of design parameters on the drive power it is necessary to carry out the calculations according to standard procedures outlined in the current technical literature. The main design parameters of the band conveyor are: the type of cargo, project performance, the geometric dimensions of sections and track configuration as a whole. The feature of band conveyor calculation as compared to the elevators is the dependence of the band width on its performance, the inclination angle and the type of cargo. In the article for the account of this fact during calculations it is necessary to construct the dependence of the band width on the generalized parameter, which takes into account change in the design parameters. To determine the general pattern of changing the value of band conveyor drive power when varying its design parameters in the article it is necessary to construct the corresponding graphic dependences taking into account the standard sizes and bands parameters. Methodology. We consider the band conveyor with two sections: the inclined and horizontal one. It is conducted a detailed analysis of dependence of the conveyor band width and its drive power on the type of cargo, project performance, geometric dimensions and configuration of the conveyor track, using the appropriate parameter dependences constructed by the authors in previous papers. Findings. For band conveyors of this type there were constructed the graphics dependences of the band width on the parameter characterizing the project performance and the inclination angle of the track section, and on the performance at a fixed angle of inclination. Taking into account the changes in the band width with an increase in the value of project performance the graph dependences of drive power on the productivity and the inclination angle of the inclined section were built. Originality. For the first time there were built the general dependences of the conveyor band width and the drive power with two sections (inclined and horizontal) on the design parameters and there were presented the corresponding graphs. Practical value. Use of the built graphic dependences of drive power of band conveyors with the inclined and horizontal sections on the design parameters makes it possible to quickly determine the approximate value of drive power at the design stage, and to determine the general change nature of its value while varying the design parameters.